Composite material based on humic acid as well as preparation method and application of composite material

By using humic acid-based composite materials in lithium-ion batteries, the problem of poor electrochemical performance of silicon-based negative electrode materials is solved, and efficient charging and discharge and long-term cycle stability is achieved.

CN119447222AInactive Publication Date: 2025-02-14СИНЬЦЗЯН ШЭНДА ИФАН БИОТЕХНОЛОДЖИ КО ЛТД
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411372252.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have poor electrochemical performance in lithium-ion batteries, especially during charging and discharging, which leads to poor circulation performance, low Coulomb efficiency, and faster battery capacity attenuation.

Method used

Using a composite material based on humic acid, mixing humic acid, urea, silicon powder with water, spray granulation and calcining, to form a silicon carbon matrix material, and nitrogen doping and polyaniline modification through polymerization reaction. Improve the electrochemical properties of materials.

Benefits of technology

The stable porous structure of silicon carbon materials has been achieved, which alleviates the volume expansion of silicon-based materials during charging and discharging, improves the charge and discharge efficiency and chemical stability, enhances the conductivity, and significantly improves the cycle stability of lithium-ion batteries. and Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067886300000071
    Figure BDA0005067886300000071
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery materials, and discloses a humic acid-based composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing humic acid, urea, silicon powder and water, carrying out spray granulation, calcining in a protective atmosphere to obtain a matrix material, and finally carrying out a polymerization reaction with an aniline monomer. According to the negative electrode material, humic acid is used as an organic carbon source, the content of oxygen-containing groups is high, a stable porous carbon structure can be formed after pyrolysis, the specific surface area is large, more space is provided for loading of silicon powder, and volume expansion of a silicon-based material is relieved. Moreover, the silicon-carbon base material is further doped with nitrogen, so that the charge-discharge efficiency of the silicon-carbon material can be effectively improved, and the chemical stability of silicon is improved. In addition, polyaniline modification is carried out, so that the conductivity of the composite material can be further enhanced, and the electrochemical performance is improved. The preparation method disclosed by the invention is simple and controllable, wide in raw material source, low in price and easy for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a humic acid-based composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + Deintercalation from the positive electrode, and then intercalation into the negative electrode through the electrolyte, the negative electrode is in a lithium-rich state; the opposite is true during discharge. At present, commercial lithium batteries usually use graphite as the negative electrode, and multi-element lithium salts such as lithium iron phosphate or lithium nickel cobalt manganese oxide as the positive electrode material. Since the graphite negative electrode has a low theoretical specific capacity (372mAh / g) and poor rate performance, it is difficult to meet the needs of the next generation of batteries.

[0003] The theoretical capacity of silicon-based materials is nearly 10 times that of graphite, and silicon-based materials have been widely studied as negative electrode materials. However, in practical applications, the conductivity of silicon negative electrodes is low, which affects the electron transfer efficiency between the positive and negative electrodes. In addition, silicon will also expand in volume during the charge and discharge process, resulting in poor cycle performance, low coulomb efficiency, and rapid battery capacity decay. In order to effectively exert the excellent performance of silicon-based materials, researchers have developed a variety of modification methods (such as carbon coating, metal modification, etc.) to improve the electrochemical properties of silicon-based materials. For example, patent CN109755483A discloses that silicon and metal are compounded by ball milling or grinding, and the material is carbon-coated in combination with pyrolysis of an organic carbon source. Its first charge and discharge capacity can reach more than 2000mAh / g, but the capacity retention rate after 50 times can only reach 50-66%, and the cycle stability is poor.

[0004] Therefore, how to effectively improve the electrochemical performance of silicon-based materials in practical applications is an urgent problem that needs to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide a humic acid-based composite material and a preparation method and application thereof, so as to solve the problem of poor electrochemical performance of silicon-based negative electrodes provided by the prior art in practical applications.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a composite material based on humic acid, comprising the following steps:

[0008] Mixing humic acid, urea, silicon powder and water to obtain slurry;

[0009] The slurry is spray-granulated to obtain precursor particles;

[0010] calcining the precursor particles under a protective atmosphere to obtain a silicon-carbon matrix material;

[0011] After the silicon-carbon matrix material is mixed with the acid solution, aniline monomer is added, and then an initiator is added to carry out polymerization reaction to obtain the humic acid-based composite material.

[0012] Preferably, in the above-mentioned method for preparing a humic acid-based composite material, the mass ratio of humic acid, urea, silicon powder and water is 1-5:0.1-1:2-7:50-200.

[0013] Preferably, in the above-mentioned method for preparing a composite material based on humic acid, the particle size of the silicon powder is 100-800 nm; and the humic acid is weathered coal humic acid.

[0014] Preferably, in the above method for preparing a composite material based on humic acid, the particle size of the precursor particles is 1 to 200 μm.

[0015] Preferably, in the above method for preparing a humic acid-based composite material, the calcination temperature is 500-800° C.; and the calcination time is 2-8 hours.

[0016] Preferably, in the above-mentioned method for preparing a composite material based on humic acid, the mass ratio of the silicon-carbon matrix material, the aniline monomer, and the initiator is 3-10:1-5:0.01-2.

[0017] Preferably, in the above method for preparing a humic acid-based composite material, the acid solution is a hydrochloric acid solution; and the concentration of the acid solution is 1 to 6 mol / L.

[0018] Preferably, in the above method for preparing a composite material based on humic acid, the temperature of the polymerization reaction is 0 to 10° C.; and the time of the polymerization reaction is 4 to 10 hours.

[0019] The invention also provides a humic acid-based composite material prepared by a preparation method of the humic acid-based composite material.

[0020] The present invention also provides a humic acid-based composite material prepared by a preparation method of a humic acid-based composite material or an application of the humic acid-based composite material in a negative electrode material for a lithium ion battery.

[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The negative electrode material of the present invention uses humic acid as an organic carbon source to form a silicon-carbon material with silicon powder. The humic acid has a high content of oxygen-containing groups and can form a stable porous carbon structure after pyrolysis. The structure has many pores and a large specific surface area, which can provide more space for the load of silicon powder and alleviate the volume expansion of the silicon-based material during the charge and discharge process. Moreover, the silicon-carbon matrix material is also nitrogen-doped, which can effectively improve the charge and discharge efficiency of the silicon-carbon material and increase the chemical stability of silicon. In addition, the present invention is also modified with polyaniline, which can further enhance the conductivity of the composite material and improve the electrochemical performance.

[0023] (2) The preparation method of the present invention is simple and controllable, the raw materials are widely available, the price is low, and it is easy to industrialize and mass produce. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a composite material based on humic acid, comprising the following steps:

[0025] Mixing humic acid, urea, silicon powder and water to obtain slurry;

[0026] The slurry is spray-granulated to obtain precursor particles;

[0027] calcining the precursor particles under a protective atmosphere to obtain a silicon-carbon matrix material;

[0028] After the silicon-carbon matrix material is mixed with the acid solution, aniline monomer is added, and then an initiator is added to carry out polymerization reaction to obtain the humic acid-based composite material.

[0029] In the present invention, the humic acid is preferably weathered coal humic acid.

[0030] In the present invention, the humic acid also includes pretreatment before use; the pretreatment method is preferably: mixing the humic acid with sodium hydroxide solution, filtering to remove the insoluble matter in the lower layer, adding hydrochloric acid solution to the upper layer solution, and then standing to produce precipitation, and the precipitation is washed with water and dried in turn to complete the pretreatment.

[0031] In the present invention, in the pretreatment method, the dosage ratio of the humic acid to the sodium hydroxide solution is preferably 1-10g:50-100mL, more preferably 4-10g:70-100mL, and more preferably 10g:90mL; the pH of the sodium hydroxide solution is preferably 10-11, and more preferably 10; the mixing method is preferably stirring; the stirring time is preferably 1-3h, and more preferably 2-3h, and more preferably 3h; the concentration of the hydrochloric acid solution is preferably 1-5mol / L, and more preferably 2-5mol / L, and more preferably 4mol / L; the hydrochloric acid solution is added until the pH of the system is preferably 2-3, and more preferably 2; the standing time is preferably 5-10h, and more preferably 6-9h, and more preferably 8h; the drying temperature is preferably 60-80°C, and more preferably 65-80°C, and more preferably 80°C; the drying time is preferably 6-12h, and more preferably 8-10h, and more preferably 8h.

[0032] In the present invention, the mass ratio of humic acid, urea, silicon powder and water is preferably 1-5:0.1-1:2-7:50-200, more preferably 3-5:0.2-0.8:3-7:100-200, and more preferably 4:0.5:7:100.

[0033] In the present invention, the particle size of the silicon powder is preferably 100 to 800 nm, more preferably 100 to 500 nm, and even more preferably 100 to 200 nm.

[0034] In the present invention, the temperature of the spray granulation is preferably 100 to 120°C, more preferably 110 to 120°C, and even more preferably 120°C.

[0035] In the present invention, the particle size of the precursor particles is preferably 1 to 200 μm, more preferably 80 to 200 μm, and even more preferably 100 to 200 μm.

[0036] In the present invention, the calcination temperature is preferably 500-800°C, more preferably 550-700°C, and more preferably 650°C; the calcination time is preferably 2-8h, more preferably 3-6h, and more preferably 4h.

[0037] In the present invention, the protective atmosphere is preferably nitrogen.

[0038] In the present invention, the mass ratio of the silicon-carbon matrix material, the aniline monomer, and the initiator is preferably 3-10:1-5:0.01-2, more preferably 5-9:1-4:0.1-1, and more preferably 7:3:0.5.

[0039] In the present invention, the initiator is preferably ammonium persulfate.

[0040] In the present invention, the acid solution is preferably a hydrochloric acid solution; the concentration of the acid solution is preferably 1 to 6 mol / L, more preferably 3 to 5 mol / L, and more preferably 4 mol / L.

[0041] In the present invention, the usage ratio of the silicon-carbon matrix material to the acid solution is preferably 3-10 g: 20-100 mL, more preferably 5-9 g: 50-80 mL, and more preferably 7 g: 60 mL.

[0042] In the present invention, the polymerization reaction temperature is preferably 0-10°C, more preferably 2-8°C, and more preferably 5°C; the polymerization reaction time is preferably 4-10h, more preferably 6-10h, and more preferably 8h.

[0043] In the present invention, after the polymerization reaction is completed, the product is centrifuged, washed and dried in sequence. The present invention does not limit the conditions for centrifugation, washing and drying, and conventional means in the art can be used.

[0044] The invention also provides a humic acid-based composite material prepared by a preparation method of the humic acid-based composite material.

[0045] The present invention also provides a humic acid-based composite material prepared by a preparation method of a humic acid-based composite material or an application of the humic acid-based composite material in a negative electrode material for a lithium ion battery.

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Example 1

[0048] This embodiment provides a method for preparing a composite material based on humic acid, comprising the following steps:

[0049] (1) Pretreatment of weathered coal humic acid: 10 g of weathered coal humic acid was mixed with 100 mL of sodium hydroxide solution with a pH of 10 for 2 h, the lower layer of insoluble matter was filtered out, and hydrochloric acid solution was added to the upper layer solution until the pH of the system was 2, and then the solution was allowed to stand for 8 h to produce precipitation, and the precipitation was washed with water and dried at 80 ° C for 10 h;

[0050] (2) mixing the weathered coal humic acid, urea and silicon powder pretreated in step (1) in water to obtain a slurry; the particle size of the silicon powder is 100 to 200 nm; the mass ratio of the weathered coal humic acid, urea, silicon powder and water is 4:0.5:5:100;

[0051] (3) spray granulating the slurry at 120° C. to obtain precursor particles with a particle size of 100 to 200 μm;

[0052] (4) calcining the precursor particles at 700° C. for 4 h under a nitrogen atmosphere to obtain a silicon-carbon matrix material;

[0053] (5) The silicon-carbon matrix material and 4 mol / L hydrochloric acid solution are mixed evenly in a ratio of 7 g:50 mL, and then aniline monomer is added and mixed evenly, and then ammonium persulfate is added and polymerized at 5°C for 6 hours. The mass ratio of the silicon-carbon matrix material, aniline monomer, and ammonium persulfate is 7:3:0.5. After the polymerization reaction is completed, the product is centrifuged, washed, and dried in sequence to obtain the humic acid-based composite material.

[0054] Example 2

[0055] This embodiment provides a method for preparing a composite material based on humic acid, comprising the following steps:

[0056] (1) Pretreatment of weathered coal humic acid see Example 1;

[0057] (2) mixing the weathered coal humic acid, urea and silicon powder pretreated in step (1) in water to obtain a slurry; the particle size of the silicon powder is 100 to 200 nm; the mass ratio of the weathered coal humic acid, urea, silicon powder and water is 3:0.1:5:50;

[0058] (3) spray granulating the slurry at 100° C. to obtain precursor particles with a particle size of 100 to 200 μm;

[0059] (4) calcining the precursor particles at 650° C. for 4 h under a nitrogen atmosphere to obtain a silicon-carbon matrix material;

[0060] (5) The silicon-carbon matrix material and 5 mol / L hydrochloric acid solution are mixed evenly in a ratio of 9 g:100 mL, and then aniline monomer is added and mixed evenly, and then ammonium persulfate is added to polymerize at 8°C for 5 hours. The mass ratio of the silicon-carbon matrix material, aniline monomer, and ammonium persulfate is 9:3:0.2. After the polymerization reaction is completed, the product is centrifuged, washed, and dried in sequence to obtain the humic acid-based composite material.

[0061] Example 3

[0062] This embodiment provides a method for preparing a composite material based on humic acid, comprising the following steps:

[0063] (1) Pretreatment of weathered coal humic acid see Example 1;

[0064] (2) mixing the weathered coal humic acid, urea and silicon powder pretreated in step (1) in water to obtain a slurry; the particle size of the silicon powder is 100 to 200 nm; the mass ratio of the weathered coal humic acid, urea, silicon powder and water is 1:1:4:100;

[0065] (3) spray granulating the slurry at 120° C. to obtain precursor particles with a particle size of 100 to 200 μm;

[0066] (4) calcining the precursor particles at 550° C. for 8 h in a nitrogen atmosphere to obtain a silicon-carbon matrix material;

[0067] (5) The silicon-carbon matrix material and 6 mol / L hydrochloric acid solution are mixed evenly in a ratio of 5 g:60 mL, and then aniline monomer is added and mixed evenly, and then ammonium persulfate is added and polymerized at 10°C for 4 hours. The mass ratio of the silicon-carbon matrix material, aniline monomer, and ammonium persulfate is 5:5:0.07. After the polymerization reaction, the product is centrifuged, washed, and dried in sequence to obtain the humic acid-based composite material.

[0068] Example 4

[0069] This embodiment provides a method for preparing a composite material based on humic acid, comprising the following steps:

[0070] (1) Pretreatment of weathered coal humic acid see Example 1;

[0071] (2) mixing the weathered coal humic acid, urea and silicon powder pretreated in step (1) in water to obtain a slurry; the particle size of the silicon powder is 400 to 600 nm; the mass ratio of the weathered coal humic acid, urea, silicon powder and water is 4:0.5:7:100;

[0072] (3) spray granulating the slurry at 120° C. to obtain precursor particles with a particle size of 100 to 200 μm;

[0073] (4) calcining the precursor particles at 800° C. for 3 h in a nitrogen atmosphere to obtain a silicon-carbon matrix material;

[0074] (5) The silicon-carbon matrix material and 2 mol / L hydrochloric acid solution are mixed evenly in a ratio of 7 g:80 mL, and then aniline monomer is added and mixed evenly, and then ammonium persulfate is added and polymerized at 0°C for 4 hours. The mass ratio of the silicon-carbon matrix material, aniline monomer, and ammonium persulfate is 7:1:1. After the polymerization reaction, the product is centrifuged, washed, and dried in sequence to obtain the humic acid-based composite material.

[0075] Comparative Example 1

[0076] This comparative example provides a method for preparing a composite material, which is specifically referred to in Example 1, except that the humic acid of weathered coal is removed.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a composite material, which is specifically referred to in Example 1, except that the weathered coal humic acid is replaced by glucose.

[0079] Comparative Example 3

[0080] This comparative example provides a method for preparing a composite material, which is specifically referred to in Example 1, except that the polyaniline modification in step (5) is removed.

[0081] The composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are respectively used as negative electrode materials for lithium-ion batteries and assembled into lithium-ion button batteries. The specific method is as follows: the composite material, carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 8:1:1, and then uniformly coated on a pure copper foil by a coating method to obtain a negative electrode; a pure lithium sheet is used as a positive electrode; the separator is Celgard2400; the electrolyte is 1M LiPF6inEC+DEC (1:1, vol%) electrolyte; and a CR2032 button battery is assembled in an argon glove box.

[0082] The electrochemical performance of the button cell prepared above was tested in the voltage range of 0.01 to 1.5 V, and the test rate was 0.2C. The test results are shown in Table 1.

[0083] Table 1 Electrochemical performance test results

[0084]

[0085] As shown in Table 1, the first coulombic efficiency of the modified silicon-carbon composite material prepared by using humic acid as the carbon source can reach 88%, and the first charge specific capacity is as high as 1100 mAh·g -1 The capacity retention rate can still be maintained at 96% after 200 cycles, which shows excellent initial capacity and cycle stability.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite material based on humic acid, characterized in that: The following steps are involved: Mixing humic acid, urea, silicon powder and water to obtain slurry; The slurry is spray-granulated to obtain precursor particles; calcining the precursor particles under a protective atmosphere to obtain a silicon-carbon matrix material; After the silicon-carbon matrix material is mixed with the acid solution, aniline monomer is added, and then an initiator is added to carry out polymerization reaction to obtain the humic acid-based composite material.

2. The method for preparing a composite material based on humic acid according to claim 1, characterized in that: The mass ratio of humic acid, urea, silicon powder and water is 1-5:0.1-1:2-7:50-200.

3. The method for preparing a composite material based on humic acid according to claim 1, characterized in that: The particle size of the silicon powder is 100-800 nm; and the humic acid is weathered coal humic acid.

4. The method for preparing a composite material based on humic acid according to claim 2, characterized in that: The particle size of the precursor particles is 1 to 200 μm.

5. The method for preparing a composite material based on humic acid according to claim 1 or 4, characterized in that: The calcination temperature is 500-800° C. and the calcination time is 2-8 hours.

6. The method for preparing a composite material based on humic acid according to claim 5, characterized in that: The mass ratio of the silicon-carbon matrix material, the aniline monomer and the initiator is 3-10:1-5:0.01-2.

7. The method for preparing a composite material based on humic acid according to claim 3, characterized in that: The acid solution is a hydrochloric acid solution; the concentration of the acid solution is 1-6 mol / L.

8. The method for preparing a composite material based on humic acid according to claim 7, characterized in that: The polymerization reaction temperature is 0 to 10° C.; the polymerization reaction time is 4 to 10 hours.

9. A humic acid-based composite material obtained by the method for preparing a humic acid-based composite material according to any one of claims 1 to 8.

10. Use of a humic acid-based composite material obtained by the preparation method of a humic acid-based composite material according to any one of claims 1 to 8 or a humic acid-based composite material according to claim 9 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method and application of silicon carbon cathode material of lithium ion battery

    CN109755483A

  • Preparation method of silicon carbon negative pole composite material

    CN106784768A

  • Conductive polymer-coated silicon composite carbon nanotube anode material and preparation method and application thereof

    CN108963227A

  • Preparation method of conductive polymer polyaniline coated porous silicon-based negative electrode material, product and application thereof

    CN111211316A

  • Nitrogen-doped carbon-coated nano ferroferric oxide composite material and preparation method thereof

    CN112331824A